DESAIN PENDIDIKAN HUMANIS-RELIGIUS - Iis Arifudin (Al-Misbah (Jurnal Islamic Studies), 2014)
Education we now have a very sharp scrutiny of the public. Our education is considered to have failed in shaping the personality of the learners. That's because, first; many phenomena frequent fighting between students, orgy, party drugs, and some acts of violence committed by a student, whether it be in school or outside of school. Second; the phenomenon of widespread culture of corruption committed by some unscrupulous Executive, Legislative, and Judiciary. Of some of the above phenomenon, there is a common thread that we can draw from the cause of the behavior disorders. According to the author, it is due to the implementation of the education we only emphasize the sheer cognitive aspects, while aspects of affective, psychomotor, and spiritually is still largely untouched. So practical education we can only give birth to a smart and intelligent, but do not have a noble character. This paper seeks to provide a solution to the problems of our national education with a design-religus humanist education. In-religious humanist education, process or means it is more important than the end or outcome. The process is more concerned with the function of education, not a forced output, also not just the pursuit of value as is currently happening in the world of our national education. In this paper described how the philosophical foundations, curriculum and materials, methods and teaching and learning, educational objectives, and evaluation model-religious humanist education.